Deviasi Orientasi Gerakan Dakwah Partai Keadilan Sejahtera: Perspektif Patologi Sosial - Setiana, Wiryo (Jurnal Ilmu Dakwah, 2009)
Stage democratizes at earth that its resident majority moslem in turn will place PKS as tilikan pulls politics developing observer at Indonesian. PKS who bases AD ARTnya ekplisits ala declares for at envy as party of mission and carries mission point in exhaustive its politics activity, on organisational ideal level it will consistence and continually fight strictly for aim attainment missionize Islam. Jeopardy that cant be avoided for any individual politics arena ingoing, party missionizes PKS this eventual has cannot but dabbled in pragmatic level while determine president candidate on general election 2009.